2021
DOI: 10.1007/s10988-020-09318-3
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of negative concord

Abstract: Concord describes a natural language phenomenon in which a single logical meaning is expressed syntactically on multiple lexical items. The canonical example is negative concord, in which multiple negative expressions are used, but a single negation is interpreted. Formally similar phenomena have been observed for the redundant marking of distributivity and definiteness. Inspired by recent dynamic analyses of these latter two phenomena, we extend a similar dynamic analysis to negative concord. We propose that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…19 To sum up, we have shown that so-called semantically expletive items are not semantically inert, because -beyond denoting an identity function-they contribute a meaning already expressed in the sentence by a c-commanding category. 20 We highlight the tendency that semantic 18 See Haddock (1987), Bumford (2017) and Kuhn (2021) for an analysis of split scope definites and other redundant forms under a dynamic semantics approach. The similarity between long weak definites and examples such as the rabbit in the hat is that the lower definite article does not contribute a presupposition of unicity and therefore can be replaced by an indefinite article.…”
Section: Semantic Expletivesmentioning
confidence: 98%
See 1 more Smart Citation
“…19 To sum up, we have shown that so-called semantically expletive items are not semantically inert, because -beyond denoting an identity function-they contribute a meaning already expressed in the sentence by a c-commanding category. 20 We highlight the tendency that semantic 18 See Haddock (1987), Bumford (2017) and Kuhn (2021) for an analysis of split scope definites and other redundant forms under a dynamic semantics approach. The similarity between long weak definites and examples such as the rabbit in the hat is that the lower definite article does not contribute a presupposition of unicity and therefore can be replaced by an indefinite article.…”
Section: Semantic Expletivesmentioning
confidence: 98%
“…NCIs are fully negative when they occur as fragment answers, in languages that have this type of items, whereas expletives cannot occur as fragments. NCIs have been claimed to introduce a discourse referent and a zero-cardinality test (Kuhn 2021), whereas none of these properties apply in the case of expletives. NCIs can be claimed to have an at-issue/truth-conditional contribution, whereas we here argue that expletives make no at-issue contribution to a proposition but may constrain one of the speech act layers.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, there have been proposals of post-suppositions that lead to falsity or ungrammaticality rather than presuppositional failure if the post-suppositional conditions are not met (e.g. Brasoveanu 2013, Kuhn 2021. I adopt the view of Charlow 2016 andKuhn 2021 that what is post-suppositional or not should be a matter of evaluation order, rather than the 'kind' of meaning.…”
Section: Introduction To Post-suppositionsmentioning
confidence: 98%
“…Brasoveanu 2013, Kuhn 2021. I adopt the view of Charlow 2016 andKuhn 2021 that what is post-suppositional or not should be a matter of evaluation order, rather than the 'kind' of meaning.…”
Section: Introduction To Post-suppositionsmentioning
confidence: 99%
See 1 more Smart Citation